Servants and masters: An activity theory investigation of human‐AI roles in the performance of work. (22nd October 2022) - Allen, Robert A.; White, Gareth R. T.; Clement, Claire E.; Alexander, Paul; Samuel, Anthony
Abstract: Organizations considering AI adoption must be mindful of media that portrays dystopian future scenarios. While machine sentience remains philosophically and ethically moot, the future implications of AI adoption are unclear. The issues that surround AI adoption need to be examined but there are a lack of implementations cases around which empirical research can be undertaken and practical experience can be gained. AI adoption needs to be considered from multiple viewpoints including, but not necessarily limited to the social, ethical and legal issues, and not merely be reduced to questions of financial return or organizational efficiency.